2010
DOI: 10.1002/jmri.22397
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evidence of altered gray and white matter microstructural development in the frontal lobe of adolescents with attention‐deficit hyperactivity disorder: A diffusional kurtosis imaging study

Abstract: Purpose To investigate non-Gaussian water diffusion using diffusional kurtosis imaging (DKI) to assess age effects on gray matter (GM) and white matter (WM) microstructural changes in the prefrontal cortex (PFC) of adolescents with attention-deficit hyperactivity disorder (ADHD) compared to typically developing controls (TDC). Materials and Methods In this preliminary cross-sectional study, T1-weighted magnetization-prepared rapid gradient echo (MPRAGE) and DKI images were acquired at 3T from TDC (n = 13) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
117
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 160 publications
(134 citation statements)
references
References 35 publications
8
117
1
2
Order By: Relevance
“…This indicates that FLE children have an impaired sensitivity to the chances of a distractor appearing and are consequently less able to resist this interference, suggesting that impairments involving frontal regions reduce the individual's ability to prepare to focus their attention on the upcoming target. Deficits in attention skills are consistent with clinical observations in children with frontal lobe injuries of different aetiology, such as tumour, stoke, cerebral marfomations, trauma (Jacobs et al, 2007), and also with imaging studies showing a reduced activation in the frontal cortex in patients with attention deficit disorder (Helpern et al, 2011). Another important function of the executive domain is cognitive flexibility.…”
Section: Wwwintechopencomsupporting
confidence: 85%
“…This indicates that FLE children have an impaired sensitivity to the chances of a distractor appearing and are consequently less able to resist this interference, suggesting that impairments involving frontal regions reduce the individual's ability to prepare to focus their attention on the upcoming target. Deficits in attention skills are consistent with clinical observations in children with frontal lobe injuries of different aetiology, such as tumour, stoke, cerebral marfomations, trauma (Jacobs et al, 2007), and also with imaging studies showing a reduced activation in the frontal cortex in patients with attention deficit disorder (Helpern et al, 2011). Another important function of the executive domain is cognitive flexibility.…”
Section: Wwwintechopencomsupporting
confidence: 85%
“…32 It has already been shown to yield valuable information about the microstructural integrity of the brain in children with epilepsy 33 and in adolescents with attention deficit/hyperactivity disorder. 34 Indeed, future DKI studies may explore the sensitivity of kurtosis metrics to pathologies that alter the microstructural complexity in the developing brain.…”
Section: Discussionmentioning
confidence: 99%
“…Using DKI measurements, Helpern's group reported less development of the frontal white matter in patients with attention-deˆcit hyperactivity disorder than in typically developing controls. 51 In addition, gray matter microstructure also lacked the signiˆcant age-related increase in complexity seen in controls; only kurtosis measures could detect this diŠerence. Therefore, the authors concluded that DKI provides information about changes in tissue microstructure that is more sensitive than and complementary to that provided by conventional diŠu-sion imaging methods.…”
Section: Neuropsychiatric Diseasementioning
confidence: 99%
“…In contrast, the use of DKI to evaluate structural changes in gray matter has been reported in relatively small numbers of subjects. 51,52 Therefore, DKI may be useful in the evaluation of NAGM in patients with multiple sclerosis. Brain MR imaging demonstrated multiple cerebral infarctions, including a subacute lesion in the right frontal deep white matter, which appeared as a high signal on diŠusion-weighted imaging (DWI) (a) and a low signal on the calculated apparent diŠusion coe‹cient (ADC) map (b).…”
Section: Multiple Sclerosismentioning
confidence: 99%